Oculto sendero An autobiographical novel of Elena Fortún: Female bildungsroman - Uribetxeberria Azpiroz, Ane (EGAN, 2021)
Oculto sendero is the autobiographical novel of the well-known Spanish writer Elena Fortún (1886-1952). She kept the novel hidden throughout her whole life and was finally published in 2016, 64 years after the passing of the writer. The aim of this paper is to verify that the novel Oculto sendero is an example of the literature subgenre bildungsroman. For this purpose, the paper describes the characteristics of the genre bildungsroman and, secondly, a comparison is carried out between those characteristics and the biographies of the main character of the Oculto sendero novel and of Elena Fortún.